Antepartum Perineal Massages is Effective to Prevent Intrapartum Perineal Rupture: Pijat Perineum Antepartum Efektif Mencegah Ruptur Perineum Intrapartum - Maria L. N. Meo (Indonesian Journal of Obstetrics and Gynecology, 2020)
Objective: To provide a summary of evidence about the benefi ts and effectiveness of perineal massage in preventing perineal rupture during labour.Methods: Evidence-based review of research articles with an evidence-based level 1a.Results: Intervention of perineal massage not only reduced the incidence of perineal rupture but also reduced the incidence of episiotomy requiring stitches, as well as reducing perineal pain after 3 months of postpartum.Conclusions: Perineal massage intervention is an intervention that is easy to do, effective, inexpensive, and has the potential to benefi t more than the potential harm in preventing perineal rupture.Keywords: intrapartum, perineal massage, perineal rupture.AbstrakTujuan: memberikan ringkasan bukti penelitian tentang manfaat dan efektifi tas dari pijat perineum dalam mencegah ruptur perineum selama persalinan.Metode: evidence-based review dengan level evidence based 1a.Hasil: Intervensi pijat perineum tidak hanya menurunkan insiden ruptur perineum tetapi juga menurunkan insiden episiotomi yang membutuhkanj jahitan, serta mengurangi nyeri perineum setelah 3 bulan postpartum.Kesimpulan: Intervensi pijat perineum merupakan intervensi yang mudah untuk dilakukan, efektif, murah, serta mempunyai potensi menguntungkan lebih banyak daripada potensi merugikan dalam mencegah ruptur perineum.Kata kunci: intrapartum, pijat perineum, ruptur perineum.